Prospects and challenges of public private partnership in car park management in Kumasi: (case of KMA and gold street real estate consult) - Ellimah, Isaac Kwame (2015)
A thesis submitted to department of Building Technology, Collage of Architecture and Planning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of MSc. Procuremen Management, 2014